BONE SCAN: A SENSITIVE MODALITY FOR DIAGNOSING A ND PREDICTING OUTCOME FOR REFLEX SYMPATHETIC DYSTROPHY - Maseeh uz Zaman; Riffat Hussain; M. Nadeem Ahmad; Khalil Khan; Gufran Khan (Journal of the Dow University of Health Sciences, 2007)
Reflex sympathetic dystrophy is a consequence o f overactive sympathetic nervous system that results in burning pain, stiftiiess, swelling and discoloration of the affected limb. Hus case report describes the condition in a man that was diagnosed with the help of radionuclide bone scan. Key words: reflex sympathetic dystrophy, complex regional pain syndrome, radionuclide bone scan.